P35 What clinical circumstances prompt hospital nurses to not administer a prescribed drug to paediatric patients?. Issue 2 (19th January 2018) - Shinh, Sunayna; West, Joanna Correa; Huynh, Chi; Terry, David; Sinclair, Anthony
Abstract : Aim: At present pharmacists and pharmacy technicians aspire to extend their role to include administering medication to in-patients. 1, 2 The aim of this research was to identify clinical factors that arise in practice that lead nurses to intentionally not-administer (omit) prescribed drugs to paediatric patients. Understanding these actions is a pre-requisite to develop non-nurse administration of drugs to hospitalised patients. Methods: Single-site, cross-sectional, qualitative study at a UK specialist paediatric hospital. The study instrument was semi-structured interviews (SSI) with hospital nurses who undertake drug administration roles. The interview questions were developed by sequential purposive discussions (4) with groups of hospital nurses. SSIs were conducted at a specialist children's hospital that provides both local secondary and tertiary care. Interviews continued until data saturation was reached; this was when no new data was collected. The data was analysed using thematic analysis to identify the themes and subthemes present in the data; facilitated by NVivo software. Approval was granted by both the study site Research Manager and the University supervising the student. Results: Ten SSIs were conducted one-to-one with paediatric nurses over a period of 2 weeks by the researcher. Eleven themes and twenty-five subthemes were identified in the data. Themes relating to reasons why prescribed drugs were intentionally omitted by nurses were: Drug rationale; 'Frequency of administration' errors/queries; 'Timing of administration'; Choice of drug; Route; Dose regimen; Symptomatic relief not required; No access available – e.g. nil by mouth or no cannula in situ; Contra–indications; Blood results; Allergy. Examples of reasons why a nurse would omit a medication under the theme 'contra-indications' were: – if the patient's clinical observations were out of range, if the medication was thought to interact with a concurrent drug or concurrent disease – e.g. if a drug would interact with a patient's condition such as patient with renal problem and non-steroidal drug prescribed. Nurses would also omit medication based on blood results, if the prescribed drug had a narrow therapeutic index and the blood concentrations were out of range. 'Phenytoin, vancomycin [and] gentamycin are the most common ones. There are other drugs such as carbamazepine as well that we tend to do more levels for now.' [Interview participant 4]. – due to the potential clinical implications that may manifest if blood concentrations exceed recommended range e.g. vancomycin accumulation can lead to nephrotoxicity. As a whole, the nurses indicated that they would intentionally omit medication if there was a concern for patient safety based on their assessment of the patient at the time of administration. Conclusion: The main reason why nurses intentionally omit medications was due to patient safety. Nurses assess patients and their prescribed drugs before deciding whether they are clinically safe and appropriate for administration, in addition to prior checks conducted by other health care practitioners. This study suggests that there are specific clinical observational skills and competencies required for staff who are involved in medicines administration to ensure the safety and effectiveness of medicines use. References: Robinson S. Hospital hires newly qualified pharmacists for wards amid nurse shortage. The Pharmaceutical Journal 23/30 May 2015;294(7863/4). [Online] doi:10.1211/PJ.2015.20068544 New ways of working for everyone. Improving medicines management by extending the roles of pharmacy technicians in mental health – A briefing document . United Kingdom Psychiatric Pharmacy Group. [online]http://www.cmhp.org.uk/wp-content/uploads/2013/02/1103_Guide-for-MH-Pharmacy-Technicians-Final-Final-30-10-08.pdf [Accessed: 8 October 2008].